ChemInform Abstract: The Iodine‐Mediated Highly Regioselective Synthesis of Angular and Linear Naphthofuroquinones. Issue 12 (March 2016) - Liu, Suyou; Long, Lijun; Xie, Duoduo; Liu, Lijun; Ma, Dayou
Abstract: A simple protocol for the iodine‐mediated cyclization of naphthoquinones (I) to afford angularly fused naphthofuroquinones (II) is developed.